2017
DOI: 10.1136/bcr-2016-219162
|View full text |Cite
|
Sign up to set email alerts
|

Safe administration of S-1 after 5-fluorouracil-induced cardiotoxicity in a patient with colorectal cancer

Abstract: Cardiotoxicity is a rare but challenging complication of 5-fluorouracil (5-FU) therapy. Compared with 5-FU, after application of S-1 lower plasma levels of the cardiotoxic metabolite alpha-fluoro-beta-alanine have been reported. Evidence for safe administration of S-1 following 5-FU cardiotoxicity is limited to a case report in an Asian patient. Herein we report the first case of S-1 application after 5-FU cardiotoxicity in a Caucasian patient.A 67-year-old man with right-sided metastatic colorectal cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…We believe that this patient did not develop cardiac toxicity on S-1 due to the fact that gimeracil is a highly active reversible DPD inhibitor; DPD inhibition by gimeracil results in significantly reduced levels of cardiotoxic catabolites of 5-FU, hence resulting in less cardiotoxicity. This is further supported by clinical experience with the use of S-1 in CRC patients with previous 5-FU-or capecitabine-induced cardiotoxicity [33,34].…”
Section: Discussionmentioning
confidence: 81%
“…We believe that this patient did not develop cardiac toxicity on S-1 due to the fact that gimeracil is a highly active reversible DPD inhibitor; DPD inhibition by gimeracil results in significantly reduced levels of cardiotoxic catabolites of 5-FU, hence resulting in less cardiotoxicity. This is further supported by clinical experience with the use of S-1 in CRC patients with previous 5-FU-or capecitabine-induced cardiotoxicity [33,34].…”
Section: Discussionmentioning
confidence: 81%
“…Nonetheless, the pathogenesis of cardiotoxicity caused by 5-FU is not clear. Actually, unchanged 5-FU elimination only represents 5–10% of the administered dose [32] and the inhibition of dihydropyrimidine dehydrogenase has been reported to be protective against the 5-FU-inflicted cardiotoxicity in humans [34,70] and in animal models [71]. Another in vitro study using keratocytes with high thymidine phosphorylase activity also showed higher 5-FU toxicity when compared to FBAL [72].…”
Section: Discussionmentioning
confidence: 99%
“…The management is symptomatic, while re-challenge does not seem an attractive and safe option (25). S-1, an oral fluoropyrimidine, consisting of tegafur, a 5-FU prodrug, oteracil potassium and gimeracil, which inhibits the degradation of 5-FU by DPD inhibition, can be possibly administered safely after capecitabine or 5-FU induced cardiotoxicity according to a limited number of case reports (38).…”
Section: Capecitabinementioning
confidence: 99%